2010
DOI: 10.1258/shorts.2010.010032
|View full text |Cite
|
Sign up to set email alerts
|

How do the information needs of cancer patients differ at different stages of the cancer journey? A cross-sectional survey

Abstract: ObjectivesProviding information to cancer patients can have significant benefits to their psychological wellbeing. The aim of this study was to investigate whether and how information needs may differ for patients at different stages of the cancer journey.DesignCross-sectional, self-completed survey using convenience sampling.SettingOncology outpatients in Wolverhampton, West Midlands.ParticipantsCancer patients aged 18 years and over.Main outcome measuresThe survey used Likert scales to determine whether pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 20 publications
(28 reference statements)
6
57
1
2
Order By: Relevance
“…context dependent and vary throughout the cancer care continuum and between individuals [4,[18][19][20][21][22]. What patients want to know does not necessarily correspond to what health care professionals think they want to know [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…context dependent and vary throughout the cancer care continuum and between individuals [4,[18][19][20][21][22]. What patients want to know does not necessarily correspond to what health care professionals think they want to know [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Providing personalized information for patients through the cancer care continuum facilitates the coping process, improves patient comfort and enhances patient choice. However, information needs often remain unmet [1][2][3][4], resulting in unrelieved symptoms and distress and unnecessary hospitalizations [5,6]. In particular, patients report substantial information deficits on therapeutic options, goals of treatment, impact of cancer on daily life, and management of symptoms of the disease [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Education, as a protective factor, was significantly associated with obsessive-compulsive tendencies and phobia symptoms. It may be the case that patients with a higher educational attainment are more likely to employ active information seeking strategies, and thus are able to satisfy their psychosocial needs (Mistry et al, 2010) and decrease their psychological distress. IVP times, another protective factor, was only associated with paranoia symptoms (OR=0.127).…”
Section: 309 Factors Associated With Psychological Characteristics Imentioning
confidence: 99%
“…In the former studies, some evidence indicates that the benefits of information provision for cancer patients include a positive impact on feelings and attitudes, improved coping ability, and a reduction in anxiety and mood disorder (Sainio et al, 2003;Mistry et al, 2010). Nevertheless, Tavoli et al (2007) performed a cross sectional study of anxiety and depression in 142 patients with gastrointestinal cancer, and found that psychiatric disorders occurred to lesser extent in patients who did not know their cancer diagnosis.…”
Section: 309 Factors Associated With Psychological Characteristics Imentioning
confidence: 99%
“…The occurrence of crc and its treatment can significantly alter an individual's nutrition needs and eating habits, because the manner in which the body digests and absorbs food is affected [14][15][16] . As a result, individuals who receive a crc diagnosis face myriad challenges while moving from one phase of the cancer trajectory to another 17 and will require specific information to better cope with the challenges. Although scps are apparently beneficial, there are pragmatic challenges in implementing them not only in crc, but also across all disease groups.…”
Section: Introductionmentioning
confidence: 99%